Flora Fountain overlooking the Central Telegraph building - Ghosh, Ayan (Jio Institute, 2023)
Historically, the circular shape of Flora Fountain acted like a roundabout for vehicular traffic. It is a prominent landmark in the heritage precinct of the Fort area, surrounded by several historical structures like Central Telegraph Office, Oriental Building, Ismail Building, Yusuf Building, and Mulla House.